Fatigue strength improvement of AISI E52100 bearing steel by induction heating and repeated quenching - Kida, K.; Honda, T.; Koike, H.; Rozwadowska, J.; Santos, E.C. (Фізико-хімічна механіка матеріалів, 2011)
Martensitic high carbon high strength AISI E52100 steel (JIS SUJ2) is one of the main alloys used in rolling contact applications when high wear and fatigue resistance are required. In this work, repeated induction heating and quenching of AISI E52100 is proposed and the refinement of the martensite structure and consequently improvement of the fatigue properties measured by rotating bending fatigue tests of steel parts is reported. Високовуглецеву високоміцну мартенситну сталь AISI E52100 (JIS SUJ2) найчастіше використовують за умов контактного кочення, де необхідні підвищені зносотривкість та втомна міцність. Запропоновано методи повторного індукційного нагріву та гартування сталі, внаслідок чого подрібнюється структура мартенситу та поліпшуються втомні властивості під час випробувань сталевих зразків за циклічного згину. Высокоуглеродистую высокопрочную мартенситную сталь AISI E52100 (JIS SUJ2) наиболее часто используют в условиях контактного качения, когда необходимы повышенные износостойкость и усталостная прочность. Предложены методы повторного индукционного нагрева и закаливания стали, вследствие чего измельчается структура мартенситна и улучшаются усталостные свойства во время испытаний стальных образцов при циклическом изгибе.